Maize farmer preferences for intercropping systems to reduce Striga in Malawi - Silberg, T.R.; Richardson, R.B.; López, M.C. (Springer, 2020)
In southern Africa the repeated cultivation of maize (Zea mays) and climate variability (especially frequent and extended droughts) have created conditions favouring parasitic weed infestation (e.g., Striga asiatica). In the past decade, Striga has reduced maize yields for smallholder farmers (cultivating less than two hectares), not only in southern Africa, but across sub-Saharan Africa (SSA). Parasitism of maize by Striga leads to significant grain yield losses. Intercropping legumes within maize-based systems has been shown to decrease Striga infestation and improve food security. Before cultivating these cropping systems, farmers consider different attributes associated with them (e.g., efforts or cost of inputs). Understanding farmers’ preferences for these attributes generates insights as how to increase adoption of intercropping as a Striga control practice. We use discrete choice experiments to identify the trade-offs which Malawian farmers are willing to accept among the attributes of choice scenarios for Striga control practices. Results indicate that farmers are willing (and in some cases unwilling) to sacrifice different fractions of maize yield for suppression of Striga, labour intensity, soil fertility and intercropped legume yield. Male and female farmers have heterogeneous preferences for these attributes. These findings have significant implications for Striga management and its effect on a crop that sustains the livelihoods of more than 80% of Malawians.